2017
DOI: 10.2139/ssrn.2968773
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Modeling and Analysis of Regional Ocean Freight Rates

Abstract: In this paper, we propose a new multivariate model for the dynamics of regional ocean freight rates. We show that a cointegrated system of regional spot freight rates can be decomposed into a common non-stationary market factor and stationary regional deviations. The resulting integrated CAR process is new to the literature. By interpreting the common market factor as the global arithmetic average of the regional rates, both the market factor and the regional deviations are observable which simplifies the cali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Chen et al [18] applied the ARIMA and the VAR approaches to predict the spot rates of several dry bulk routes and found out that the VAR approach performed better than the ARIMA approach in test-sample forecasts. Adland et al [19] showed a cointegration-based method for analyzing regional ocean freight rates' dynamic properties.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Chen et al [18] applied the ARIMA and the VAR approaches to predict the spot rates of several dry bulk routes and found out that the VAR approach performed better than the ARIMA approach in test-sample forecasts. Adland et al [19] showed a cointegration-based method for analyzing regional ocean freight rates' dynamic properties.…”
Section: Literature Reviewmentioning
confidence: 99%